Accountability for Management of Village-Owned Enterprises (BUMDES) Tanjung Raya in Boyan Tanjung Village, Boyan Tanjung District, Kapuas Hulu Regency - Melati, Sephana Suramaga; Pudjianto, S.Y.; Sulisdiani, Indah; Marini, Marini (Pancasila International Journal of Applied Social Science, 2024)
This research was conducted because there was no accountability for the management of Tanjung Raya BUMDes, Boyan Tanjung Village, Boyan Tanjung District, Kapuas Hulu Regency. The method used is descriptive qualitative. Researchers use the theory proposed by David Hulme and Mark Tuner, namely there are six indicators, with four research subjects. The purpose of this study is to describe, analyze the accountability of the management of Village-Owned Enterprises (BUMDes) by Tanjung Raya BUMDes managers. The results of this study show that there are six discussions, first, management accountability in terms of legitimacy can be concluded that this is not optimal, it can be seen from the management of Tanjung Raya BUMDes Boyan Tanjung Village is not elected through elections involving the community. Second, the accountability of Tanjung Raya BUMDes management in terms of moral quality can be concluded that it has not been optimal as seen from the BUMDes managers who resigned unofficially. third, accountability for the management of Tanjung Raya BUMDes in terms of sensitivity can be concluded that it has not been optimal as seen from the non-development of new business units by the manager. Fourth, accountability of Tanjung Raya BUMDes management in terms of openness can be concluded that it has not been optimal because BUMDes managers do not regularly report and lack coordination with the Village Government. Fifth, management accountability in terms of resource utilization can be concluded not optimal seen from the manager not utilizing existing resources in Boyan Tanjung Village, the last management accountability in terms of effectiveness and efficiency can be said to be not optimal, this can be seen from the inactivity of BUMDes managers so that they are assisted by the village government in developing business units. It is hoped that the accountability applied will be able to help the development of Tanjung Raya BUMDes.